Insights from School Oral Health Program in Sudan 2023: A Model for Public Health Planning, Intervention and Evaluation - Motaz Ibrahim Suliman; Alaa Abuelgasim Mohamed; Ahmed Obaid; Omer Babiker; Ammar Hussien; Alameen O. Abusham; Braa Malik (Disease and Health: Research Developments Vol. 5, 2025)
This chapter examines the development, implementation, and assessment of a school-based oral and dental health program in Sudan, highlighting its impact on public health. The initiative aimed to improve oral health outcomes among primary school children through structured interventions, including preventive education, clinical screenings, and fluoride-based treatments. The chapter details the strategic planning process, including school selection, resource allocation, and ethical considerations, ensuring a community-centered approach. Clinical assessments involved standardized screening methodologies to evaluate oral health status among 1599 school children from six primary schools, followed by targeted interventions such as fluoride varnish application and referral systems for necessary treatments. The finding of the survey showed DMFT average score of 1.69 and CPI average score of 1.49. The evaluation framework incorporated pre- and post-intervention surveys, stakeholder feedback, and longitudinal data analysis to measure effectiveness and dental students performance assessment throughout the program. The findings emphasize significant improvements in oral health awareness and preventive behaviors among schoolchildren with 89.4% service coverage and 1033 referred cases for further on site dental tratement, reinforcing the necessity of policy integration and sustainable community involvement. The chapter concludes with recommendations for expanding similar programs within Sudan and beyond, advocating for strengthened public health strategies and collaborative partnerships in school-based dental health initiatives.